ROLE OF ENVIRONMENTAL PROACTIVITY IN PERFORMANCE OF MANUFACTURING FIRMS: A MODERATING EFFECT OF FIRM SIZE - Afshan Azam vv; Kashif Munir; Ibrahim Abdullah (MATTER: International Journal of Science and Technology, 2025)
This study investigates the effect of environmental proactivity on the performance of firms. The performance of firms has been checked through the relationship between environmental proactivity with operational performance as well as perceived financial performance. The study is also investigating the moderating effect of firm size between performance of firm and environmental proactivity. The data has been collected from adopted questionnaires which are being used by previous researchers. Questionnaires are being used for investigation of this study. Middle level managers of manufacturing firms of cities including Lahore, Sheikhupura, Faisalabad and Kasur are being used for filling questionnaires. All manufacturing firms has been used for this investigation which may affect the environment because of their procedures of production. Closes ended questions are used in this study. Although, open ended single question was being included for specific answer for the measurement of firm size. Companies have been selected in this study on the basis of convenient sampling. Cronbach Alpha is used for checking the reliability of scale. Composite reliability is also checked. To test the hypothesis of effect of environment proactivity on firms’ performance and moderating role of firm size, partial least square structural equation modelling is being applied. Among environment proactivity and firm performance, significant and positive relationship has been found. It has been found that there is weak moderation effect of firm size among environment proactivity and firm performance. Especially, there is more effective moderation with operational performance than perceived financial performance of firms. The study has suggested to investigate the compliance of ISO 14001 within context of Pakistan for further studied.